2023
DOI: 10.1159/000533177
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Management Performance of ChatGPT in Obstetrics and Gynecology

Abstract: <b><i>Objectives:</i></b> The use of artificial intelligence (AI) in clinical patient management and medical education has been advancing over time. ChatGPT was developed and trained recently, using a large quantity of textual data from the internet. Medical science is expected to be transformed by its use. The present study was conducted to evaluate the diagnostic and management performance of the ChatGPT AI model in obstetrics and gynecology. <b><i>Design:</i></b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Although some research suggests that ChatGPT needs to be specifically trained in the medical field to be effective ( 3 ). a substantial body of research has already demonstrated the excellent capabilities of ChatGPT in the medical field ( 4 , 5 ).…”
mentioning
confidence: 99%
“…Although some research suggests that ChatGPT needs to be specifically trained in the medical field to be effective ( 3 ). a substantial body of research has already demonstrated the excellent capabilities of ChatGPT in the medical field ( 4 , 5 ).…”
mentioning
confidence: 99%
“…After screening, 54 studies were included in the metaanalysis of generative AI diagnostic performance 12,13, and 13 studies in the comparative analysis between generative AI models and physicians (Figure 1 and Table 1). 32,33,[35][36][37][38][39][40][41]49,52,58,62 The most evaluated models were GPT-4 4 (31 articles) and GPT-3.5 (28), while models such as GPT-4V ( 6), PaLM2 8 (3), Llama 2 6 (2), Prometheus (2), GPT-3 3 (1), Glass ( 1 were represented, as well as Gastroenterology, Cardiology, Pediatrics, Otolaryngology, Urology, Endocrinology, Gynecology, Orthopedic surgery, Rheumatology, Psychiatry, and Plastic surgery with one article each. Regarding model tasks, free text tasks were the most common, with 47 articles, followed by choice tasks at 13.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Allahqoli et al [ 16 ] reported a series of cases of OBGYN that were presented to ChatGPT, and their diagnostic and management performances were compared with those of a gynecologist. The results of 30 cases were provided, including early pregnancy, general gynecology, emergency gynecology obstetrics, peripartum care, obstetric emergencies, family planning, and sexual health, adapted from the book titled ‘100 cases in Obstetrics and Gynecology’.…”
Section: Chatgpt In Obgyn: Diagnostic Advancementsmentioning
confidence: 99%